PENGARUH CANVASSING TERHADAP PENJUALAN PRODUK KUR SYARIAH DI PT PEGADAIAN CABANG SWETA - Dana, Kadek Prayoga Merta; Sukendri, Nengah; Pancawati, Ni Luh Putu Anom (Waisya : Jurnal Ekonomi Hindu, 2025)
The success of pawnshops in achieving their goals is very dependent on marketing strategies so that their products can be accepted and sold in the market. In the face of increasingly fierce competition, pawnshops, especially the Sweta branch, need to continue to improve product quality to attract and retain customers in order to achieve sales targets. In introducing and promoting sharia KUR products to prospective borrowers PT. Pegadaian Sweta Branch implements an effective marketing strategy, namely canvassing. Activity canvassing is a direct marketing activity in the form of promotions as carried out by PT employees. Sweta Branch Pawnshop by visiting potential customers directly to introduce and offer products available at the pawnshop. This research aims to test the effect canvassing on sales of sharia KUR products at PT. Sweta Branch Pawnshop and test how big the influence is canvassing on sales of sharia KUR products at PT. Sweta Branch Pawnshop. This research uses an associative quantitative approach. The sample in this study was 47 respondents who were employees of PT. Sweta Branch Pawnshop. The research results show that there is a positive and significant influence on canvassing regarding sales of sharia KUR products, this can be proven from the results of the t test that the t-calculated value is 10.628 > the t-table value, namely 1.6794. And the significant value is 0.000 < 0.05 which means that the hypothesis (Ha) is accepted and the hypothesis (H0) is rejected. Furthermore canvassing has a strong influence on sales of KUR sharia products at PT. Sweta Branch Pawnshop. It can be seen from the R Square value that it is 71% and the remaining 28.5% is influenced by other variables that were not studied.